Paisagem e percepção ambiental: uma análise acerca das transformações antropogênicas no distrito do Pecém – São Gonçalo do Amarante (Ceará) - Castro, Lígia Maria Silva Pereira (2021)
This research focuses on the district of Pécem, which has undergone a high level of socio-environmental change from the Complexo Industrial e Portuário do Pecém (CIPP). The general objective of the research is to identify and analyze the environmental perception of the residents about the socio-environmental transformations generated by the developments installed in the area, and also to detect the transformations in the landscapes as a result of anthropic interventions. The methodology starts from an integrated vision, having as a guiding principel two theoretical matrices to reach the proposed objectives: Environmental Perception and Landscape Analysis. The degree and character of the impact of human activities on the landscape has been analyzed from the numerical definition of the anthropogenic charge to which a given landscape is subjected, through the use of Shidhenko’s (1988) Anthropogenic Transformation Coefficient (Kan). The identification of the environmetal perception of the selected individuals was carried out by applying structured questionnaires and conducting interviews. As for the results, the units were classified into three stages of ecological exploration. The Faixa de praia/Campo de dunas/Complexo flúvio-marinho unit (Kan=6.31), it is an area considered of mild anthropogenic changes, the Depressão sertaneja unit (Kan=38.47) is an area with a moderate degree of anthropogenic modification, and the Tabuleiro costeiro is configured as an environment of strong anthropogenic modification (Kan=70.33). The panorama of the environmental perception of residents seen in this paper shows the importance of social actors in the diagnosis of problems and in proposing solutions to adversities, highlighting the relevance of true popular participation in th contribution of the management of their territories. The population started to live daily with constant transformations, whether in the physical space or in the cutural field, inlfuencing the construction of a new identity and adapting to the dynamics of the globalizing logic in function of the implementation of the industrial park.